Aesthetic problem in the appearance of permanent teeth in children and adolescents - dental fluorosis. - Luchowska, Anna; Sroczyńska, Monika; Żaczek, Aleksandra (Journal of Education, Health and Sport, 2022)
Introduction: Dental fluorosis is a disease caused by excessive consumption of fluoride and its deposition in the enamel during odontogenesis. The result of this process is the appearance on the surface of permanent teeth of unsightly stains of various colors depending on the intensity of damage to the enamel. Deterioration of dental aesthetics can significantly affect the quality of life of patients affected by dental fluorosis. Aim of the study: The purpose of this study is to present contemporary knowledge on the cause, diagnosis and treatment of dental fluorosis. Materials and methods: Medical databases of the National Center for Biotechnology Information/PubMed and Google Scholar were analyzed by typing the following keywords: dental fluorosis, fluoride poisoning, amelogenesis, enamel. When analyzing the literature, data from 25 scientific articles from the last five years (2017-2022) were used. Results: In most of the articles, the authors emphasize the significant association between consumption of fluoridated water and fluorosis of permanent teeth. The literature is unanimous regarding the choice of minimally invasive treatment procedures when dental fluorosis needs to be treated. Conclusions: Dental fluorosis is a significant aesthetic and functional problem among affected children. Education about the etiology of dental fluorosis and ways to avoid it should be constantly disseminated among children's caregivers. Patients affected by this problem should be under the constant care of a dentist.